EVALUASI FORMATIF BAHAN SIARAN RADIO PENDIDIKAN PROGRAM PENYETARAAN D II GURU SEKOLAH DASAR DAN DIKLAT SIARAN RADIO PENDIDIKAN (SRP) - Abdul Gafur (Jurnal Cakrawala Pendidikan, 2003)
This article is based on an evaluative research intended todetermine the quality profileof the educational radio programsproduced by PUSTEKKOM DIKBUD, a center for communicationtechnology for education, from the pointof view of instructionalaspects, the popularityof the media, and the listeners' level ofunderstanding.Thirty-two pre-recorded educational programsin the format ofaudiocassettes were selected for field evaluation/testing. For thepurposeof the field evaluation, sixty elementary school teachersfrom three provinces (Central Java, Central Kalimantan,and EastNusa Tenggara), with twentyfrom each province, were selected assubjects for the field evaluation. For three days, each group oftwenty teachers were assigned to listen to 10- I2 of the radioprograms. After listeningto each program, they were asked to fill outa questionnaire and interviewedin order that information of theiropinions, impressions, and understandingof the programs could beobtained.The findings show that in general the qualityof the radioprograms from the pointof view of their instructional aspects wasgood enough (that is, the instructional objectives were clearly stated,the contentsofthe lessons were relevant with the achievement oftheobjectives, etc.). From the pointof view of the instructional media, the programs were interesting (the musical background wasinteresting and the presentations were helpful enough for theunderstandingof the contents of the lessons). Only some of theprograms were considered low in quality and in needofrevision.On the basisof the results of the evaluation, it is suggested thatbefore being broadcast nationally, eachof the radio programs shouldbe field testedto get information about its strengths and weaknessesso that the program developer and producer can revise and improvethem